Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Probing Iron-Ligand interactions by combining modern high-resolution hard X-ray spectroscopy and density functional theory : a powerful methodology in cases where conventional methods fail / vorgelegt von Lukas Burkhardt ; [Prof. Dr. Matthias Bauer (Erstgutachter), Prof. Dr. Thomas Kühne (Zweitgutachter), Jun. Prof. Dr. Stephan Hohloch (Drittprüfer)] - Burkhardt, Lukas

Experimental and theoretical (high energy resolution) X-ray absorption and emission spectroscopy / vorgelegt von Patrick Müller ; [Promotionskommission: Prof. Dr.-Ing. Hans-Joachim Warnecke, Vorsitz; Prof. Dr. Matthias Bauer, Erstgutachter; Prof. Dr. Thomas D. Kühne, Zweitgutachter; Prof. Dr. Wolf Gero Schmidt] - Müller, Patrick

A von Hamos-type hard X-ray spectrometer at the PETRA III beamline P64 - Kalinko, Aleksandr; Caliebe, Wolfgang A.; Schoch, Roland; Bauer, Matthias (Journal of Synchrotron Radiation)
The design and performance of the high-resolution wavelength-dispersive multi-crystal von Hamos-type spectrometer at PETRA III beamline P64 are described. Extended analyzer crystal collection available at the beamline allows coverage of a broad energy range from 5 keV to 20 keV with an energy resolution of 0.35–1 eV. Particular attention was paid to enabling two-color measurements by a combination of two types of analyzer crystals and two two-dimensional detectors. The performance of the spectrometer is demonstrated by elastic-line and emission-line measurements on various compounds.
Keywords: Instrumentation; Nuclear and High Energy Physics; Radiation

Gold(ii) in redox-switchable gold(i) catalysis - Veit, Philipp; Volkert, Carla; Förster, Christoph; Ksenofontov, Vadim; Schlicher, Steffen; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Gold(ii) species catalyse the cyclisation of N(2-propyn-1-yl)benzamide to 2-phenyl-5-vinylidene-2-oxazoline without halide abstraction while the neutral gold(i) complex is inactive indicating a gold(ii/i) redox-switch.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Improving Selectivity and Activity of CO2 Reduction Photocatalysts with Oxygen - Kreft, Stefanie; Schoch, Roland; Schneidewind, Jacob; Rabeah, Jabor; Kondratenko, Evgenii V.; Kondratenko, Vita A.; Junge, Henrik; Bauer, Matthias; Wohlrab, Sebastian; Beller, Matthias (Chem)
Keywords: Materials Chemistry; Biochemistry (medical); General Chemical Engineering; Environmental Chemistry; Biochemistry; General Chemistry

Excited‐State Kinetics of an Air‐Stable Cyclometalated Iron(II) Complex - Steube, Jakob; Burkhardt, Lukas; Päpcke, Ayla; Moll, Johannes; Zimmer, Peter; Schoch, Roland; Wölper, Christoph; Heinze, Katja; Lochbrunner, Stefan; Bauer, Matthias (Chemistry – A European Journal)

Stereoselective Alkyne Hydrogenation by using a Simple Iron Catalyst - Gregori, Bernhard J.; Schwarzhuber, Felix; Pöllath, Simon; Zweck, Josef; Fritsch, Lorena; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Hard X-ray spectroscopy: an exhaustive toolbox for mechanistic studies (?) - Schoch, Anke; Burkhardt, Lukas; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias (Faraday Discussions)
The hard X-ray spectroscopy methods XAS, valence-to-core XES and higher solution XANES offer unique insights into organometallic reaction mechanisms.

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)

Towards Noble-Metal-Free Dyads: Ground and Excited State Tuning by a Cobalt Dimethylglyoxime Motif Connected to an Iron N-Heterocyclic Carbene Photosensitizer - Zimmer, Peter; Burkhardt, Lukas; Schepper, Rahel; Zheng, Kaibo; Gosztola, David; Neuba, Adam; Flörke, Ulrich; Wölper, Christoph; Schoch, Roland; Gawelda, Wojciech; Canton, Sophie E.; Bauer, Matthias (European Journal of Inorganic Chemistry)

Eisenbasierte Photosensitizer für die Photokatalyse / vorgelegt von Dipl.-Chem. Peter Zimmer ; [Prof. Dr. Thomas Kühne (Vorsitz), Prof. Dr. Matthias Bauer (Erstgutachter), Jun.-Prof. Dr. Stephan Hohloch (Zweitgutachter), Priv.-Doz. Dr. Hans Egold] - Zimmer, Peter

High energy resolution X-ray absorption and emission based studies on the mononuclear spin crossover complex [Fe(L-N4Bn2)(NCS)2] / vorgelegt von Dipl.-Chem. Rahel Schepper ; [Prof. Dr.-Ing. Hans-Joachim Warnecke (Kommissionsvorsitz), Prof. Dr. Matthias Bauer (Erstgutachter), Jun.-Prof. Dr. Stephan Hohloch (Zweitgutachter), Prof. Dr. Thomas Kühne (Drittprüfer)] - Schepper, Rahel

Structural dynamics upon photoexcitation-induced charge transfer in a dicopper(i)–disulfide complex - Naumova, Maria; Khakhulin, Dmitry; Rebarz, Mateusz; Rohrmüller, Martin; Dicke, Benjamin; Biednov, Mykola; Britz, Alexander; Espinoza, Shirly; Grimm-Lebsanft, Benjamin; Kloz, Miroslav; Kretzschmar, Norman; Neuba, Adam; et al. (Physical Chemistry Chemical Physics)
A study of structural evolution upon photoinduced charge transfer in a dicopper complex with biologically relevant sulfur coordination.

Developing intercalation based anode materials for fluoride-ion batteries: topochemical reduction of Sr2TiO3F2via a hydride based defluorination process - Wissel, Kerstin; Dasgupta, Supratik; Benes, Alexander; Schoch, Roland; Bauer, Matthias; Witte, Ralf; Fortes, Andrew Dominic; Erdem, Emre; Rohrer, Jochen; Clemens, Oliver (Journal of Materials Chemistry A)
Sr2TiO3F2−x, a potential anode material for fluoride ion batteries, is prepared in the charged state via selective low-temperature defluorination.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Chromium Complexes with Oxido and Corrolato Ligands: Metal-Based Redox Processes versus Ligand Non-Innocence - Garai, Antara; Sobottka, Sebastian; Schepper, Rahel; Sinha, Woormileela; Bauer, Matthias; Sarkar, Biprajit; Kar, Sanjib (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Syntheses of ruthenium complexes for studies on water oxidation and their immobilization approaches - Söyler, Hatice

Photocatalytic water reduction systems based on iridium and non-noble metal complexes - Tünnermann, Maike

Diferrate [Fe2(CO)6(μ-CO){μ-P(aryl)2}]− as Self-Assembling Iron/Phosphor-Based Catalyst for the Hydrogen Evolution Reaction in Photocatalytic Proton Reduction-Spectroscopic Insights - Fischer, Steffen; Rösel, Arend; Kammer, Anja; Barsch, Enrico; Schoch, Roland; Junge, Henrik; Bauer, Matthias; Beller, Matthias; Ludwig, Ralf (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Understanding and exploiting long-lived near-infrared emission of a molecular ruby - Otto, Sven; Dorn, Matthias; Förster, Christoph; Bauer, Matthias; Seitz, Michael; Heinze, Katja (Coordination Chemistry Reviews)
Keywords: Materials Chemistry; Physical and Theoretical Chemistry; Inorganic Chemistry

Structure–function relationship during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts under atmospheric pressure conditions - Martin, Natalia M.; Hemmingsson, Felix; Wang, Xueting; Merte, Lindsay R.; Hejral, Uta; Gustafson, Johan; Skoglundh, Magnus; Meira, Debora Motta; Dippel, Ann-Christin; Gutowski, Olof; Bauer, Matthias; Carlsson, Per-Anders (Catalysis Science & Technology)
Intermediate species formed during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts.
Keywords: Catalysis

A Straightforward Synthesis to Novel 1,10-Phenanthrolines with Fused Thiophene Structure - Bauer, Matthias; Tünnermann, Maike; Rehsies, Pia; Flörke, Ulrich (Synlett)
We report here a straightforward synthesis for a series of new structures with fused 1,10-phenanthroline-thiophene connection. They are synthesized with a modified Hinsberg thiophene procedure, followed by successive modification to yield several 5,7-disubstituted thieno[3,4-f][1,10]phenanthrolines, most notable thiophene-substituted compounds that could be potentially of use for organic electronics applications. For some selected examples, crystal structures were obtained, showing a nearly coplanar arrangement around the fused connection, also beneficial for an effective electron transfer in organic electronics or solar cells.
Keywords: Organic Chemistry

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Entwicklung und Synthese von Ein- und Mehrkomponentensystemen zur photokatalytischen Wasserreduktion - Meinhardt, Regina

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Detection and Characterization of Hydride Ligands in Iron Complexes by High-Resolution Hard X-ray Spectroscopy and Implications for Catalytic Processes - Burkhardt, Lukas; Holzwarth, Michael; Plietker, Bernd; Bauer, Matthias (Inorganic Chemistry)

Structure and reactivity of a mononuclear gold(II) complex - Preiß, Sebastian; Förster, Christoph; Otto, Sven; Bauer, Matthias; Müller, Patrick; Hinderberger, Dariush; Hashemi Haeri, Haleh; Carella, Luca; Heinze, Katja (Nature Chemistry)

Phenanthroline-basierte Kupferkomplexe für Wasserspaltungsanwendungen - Stührenberg, Kai

Catalytic hydrogenation of CO2 to methane over supported Pd, Rh and Ni catalysts - Martin, Natalia M.; Velin, Peter; Skoglundh, Magnus; Bauer, Matthias; Carlsson, Per-Anders (Catalysis Science & Technology)
CO2 methanation over Rh/Al2O3, Rh/CeO2 and Ni/CeO2 at 350 °C highlighting the different surface speciation during reaction.
Keywords: Catalysis

Structural Transitions and Thermochromism of Linear Polynuclear Cobalt(II)-4-Octadecyl-1,2,4-triazole Complexes - Bräunlich, Irene; Mair, Christiane; Bauer, Matthias; Caseri, Walter (Journal of Inorganic and Organometallic Polymers and Materials)
Keywords: Materials Chemistry; Polymers and Plastics

The Connection between NHC Ligand Count and Photophysical Properties in Fe(II) Photosensitizers: An Experimental Study - Zimmer, Peter; Burkhardt, Lukas; Friedrich, Aleksej; Steube, Jakob; Neuba, Adam; Schepper, Rahel; Müller, Patrick; Flörke, Ulrich; Huber, Marina; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)

N-Heterocyclic Carbene Complexes of Iron as Photosensitizers for Light-Induced Water Reduction - Zimmer, Peter; Müller, Patrick; Burkhardt, Lukas; Schepper, Rahel; Neuba, Adam; Steube, Jakob; Dietrich, Fabian; Flörke, Ulrich; Mangold, Stefan; Gerhards, Markus; Bauer, Matthias (European Journal of Inorganic Chemistry)

Experimental and Theoretical High-Energy-Resolution X-ray Absorption Spectroscopy: Implications for the Investigation of the Entatic State - Vollmers, Nora Jenny; Müller, Patrick; Hoffmann, Alexander; Herres-Pawlis, Sonja; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe; Bauer, Matthias (Inorganic Chemistry)

Pollution Control Meets Sustainability: Structure-Activity Studies on New Iron Oxide-Based CO Oxidation Catalysts - Schoch, Roland; Bauer, Matthias (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

Molecular dynamics and reverse Monte Carlo modeling of scheelite-type AWO4(A = Ca, Sr, Ba) WL3-edge EXAFS spectra - Kalinko, Aleksandr; Bauer, Matthias; Timoshenko, Janis; Kuzmin, Alexei (Physica Scripta)
Keywords: Condensed Matter Physics; Mathematical Physics; Atomic and Molecular Physics; and Optics

Efficient Biomimetic Hydroxylation Catalysis with a Bis(pyrazolyl)imidazolylmethane Copper Peroxide Complex - Wilfer, Claudia; Liebhäuser, Patricia; Hoffmann, Alexander; Erdmann, Hannes; Grossmann, Oleg; Runtsch, Leander; Paffenholz, Eva; Schepper, Rahel; Dick, Regina; Bauer, Matthias; Dürr, Maximilian; Ivanović-Burmazović, Ivana; et al. (Chemistry - A European Journal)

Experimentelle und theoretische Untersuchung der Existenz von CuII, CuIIIund CuIVin Kupfercorrolen - Sinha, Woormileela; Sommer, Michael G.; Deibel, Naina; Ehret, Fabian; Bauer, Matthias; Sarkar, Biprajit; Kar, Sanjib (Angewandte Chemie)
Keywords: General Medicine

Cocatalyst Designing: A Regenerable Molybdenum-Containing Ternary Cocatalyst System for Efficient Photocatalytic Water Splitting - Busser, G. Wilma; Mei, Bastian; Weide, Philipp; Vesborg, Peter C. K.; Stührenberg, Kai; Bauer, Matthias; Huang, Xing; Willinger, Marc-Georg; Chorkendorff, Ib; Schlögl, Robert; Muhler, Martin (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Cobalt-based nanocatalysts for green oxidation and hydrogenation processes - Jagadeesh, Rajenahally V; Stemmler, Tobias; Surkus, Annette-Enrica; Bauer, Matthias; Pohl, Marga-Martina; Radnik, Jörg; Junge, Kathrin; Junge, Henrik; Brückner, Angelika; Beller, Matthias (Nature Protocols)
Keywords: General Biochemistry; Genetics and Molecular Biology

Experimental and Theoretical Investigations of the Existence of CuII, CuIII, and CuIVin Copper Corrolato Complexes - Sinha, Woormileela; Sommer, Michael G.; Deibel, Naina; Ehret, Fabian; Bauer, Matthias; Sarkar, Biprajit; Kar, Sanjib (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

High-resolution X-ray absorption spectroscopy of iron carbonyl complexes - Atkins, Andrew J.; Bauer, Matthias; Jacob, Christoph R. (Physical Chemistry Chemical Physics)
We apply high-energy-resolution fluorescence-detected (HERFD) X-ray absorption near-edge structure (XANES) spectroscopy to study iron carbonyl complexes.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Configuration Determination of Transition Metal Complexes by Multiple Scattering EXAFS Analysis: A Case Study - Bauer, Matthias (Zeitschrift für Physikalische Chemie)
A multiple scattering extended X-ray absorption fine structure (EXAFS) analysis of Ti(acac) 2 Cl 2 is presented. With such an approach the configuration of the ligands in this complex can be identified due to the different multiple scattering events in the cis - and trans -configuration. A thorough evaluation of the effects of the different multiple scattering parameters (effective scattering path, scattering order, number of scattering atoms) in combination with the input structure is presented that reveals a complicated correlation between these parameters which could lead to wrong results with respect to the determined configuration. Finally, the optimal procedure for this particular purpose is defined and described.
Keywords: Physical and Theoretical Chemistry

Gels, xerogels and films of polynuclear iron(ii)–aminotriazole spin-crossover polymeric complexes - Sánchez-Ferrer, Antoni; Bräunlich, Irene; Ruokolainen, Janne; Bauer, Matthias; Schepper, Rahel; Smith, Paul; Caseri, Walter; Mezzenga, Raffaele (RSC Adv.)
Keywords: General Chemical Engineering; General Chemistry

BOX Ligands in Biomimetic Copper‐Mediated Dioxygen Activation: A Hemocyanin Model - Walli, Adam; Dechert, Sebastian; Bauer, Matthias; Demeshko, Serhiy; Meyer, Franc (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

A New Iron-Based Carbon Monoxide Oxidation Catalyst: Structure-Activity Correlation - Schoch, Roland; Huang, Heming; Schünemann, Volker; Bauer, Matthias (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Design of Highly Porous Single‐Site Catalysts through Two‐Step Postsynthetic Modification of Mixed‐Linker MIL‐53(Al) - Gotthardt, Meike A.; Schoch, Roland; Brunner, Tobias S.; Bauer, Matthias; Kleist, Wolfgang (ChemPlusChem)
Keywords: General Chemistry

Synthesis and characterization of bimetallic metal–organic framework Cu–Ru-BTC with HKUST-1 structure - Gotthardt, Meike A.; Schoch, Roland; Wolf, Silke; Bauer, Matthias; Kleist, Wolfgang (Dalton Transactions)
A mixed-metal framework Cu–Ru-BTC with the formula Cu2.75Ru0.25(BTC)2·xH2O was successfully synthesized. Partial substitution of Cu2+ by Ru3+ in the paddlewheel structure was proven using X-ray absorption spectroscopy.
Keywords: Inorganic Chemistry

A Rhodium Triphenylphosphine Catalyst for Alkene Hydrogenation Supported on Neat Superparamagnetic Iron Oxide Nanoparticles - Dehe, Daniel; Wang, Lei; Müller, Melanie K.; Dörr, Gunder; Zhou, Zhou; Klupp-Taylor, Robin N.; Sun, Yu; Ernst, Stefan; Hartmann, Martin; Bauer, Matthias; Thiel, Werner R. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Hydrolytic Stability and Hydrogen Peroxide Activation of Zirconium‐Based Oxoclusters - Faccioli, Francesco; Bauer, Matthias; Pedron, Danilo; Sorarù, Antonio; Carraro, Mauro; Gross, Silvia (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry